Avian functional group responses to rainfall across four vegetation types in the Simpson Desert, central Australia. (15th July 2013) - Tischler, Max; Dickman, Christopher R.; Wardle, Glenda M.
Abstract Temporal and spatial variability in rainfall and subsequent resource flows often drive large changes in bird demography and the structure of avian assemblages in arid regions. Here, we describe broad avian functional group responses to rainfall across four vegetation classes in the Simpson Desert, central Australia, over a period when both dry and wet conditions prevailed. Birds were surveyed in eucalypt woodlands, gidyea woodlands, mixed Acacia (mulga) shrublands and spinifex‐dominated hummock grasslands in this region between 2006 and 2008 using a spatially nested hierarchical sampling design with fixed radius point counts as replicates. Predictably, the composition of bird communities varied across vegetation classes as well as over time. Generalist feeders and insectivorous birds dominated assemblages during dry periods, whereas granivorous species were most abundant and widespread following heavy rains. Carnivores and specialist nectarivores responded variably throughout the sampling period regardless of habitat. The dynamics of granivores were especially interesting; large numbers of nomadic species moved into the study area in response to rainfall, highlighting a key role for this group in shaping community structure. This study represents the first attempt to investigate avian functional group dynamics across differing vegetation types in a variable but low productivity landscape. The findings confirm that community composition is spatially and temporally dynamic, and prompt further investigation into the roles that habitat and resource limitation play in defining bird communities in arid Australia.